Revalorización de la jícama (Smallanthus sonchifolius) proveniente de la Red Agroecológica de la ciudad de Loja, mediante la elaboración de un subproducto deshidratado - Patiño Armijos, Jenniffer Andrea (2023)
Jicama (Smallanthus sonchifolius) It is a crop that has a high nutritional content, however, over time its use has been devalued due to ignorance. Due to this, a study was carried out to revalue jicama through the elaboration of a dehydrated by-product. For this, the raw material was obtained from the farms of the San Lucas parish of the Agroecological Network of Loja, then the samples were dehydrated, using 3 temperatures 50, 55 and 60 °C and 3 times 10, 12 and 14 hours of dehydration. In the data analysis, the completely randomized experimental design (DCA) was applied with a 3 x 3 bifactorial arrangement. The optimal dehydration conditions for jicama were obtained from the organoleptic analysis, which was carried out by 9 panelists, using a 5-point hedonic scale; In addition, the nutritional content of the jicama by-product with better acceptability was determined. The results showed that T6 was the one that obtained the highest qualifications with the following averages: color 4.56; flavor 4.78; texture 4.78 and acceptability 4.44. With these results, it is established that the optimum temperature and dehydration time were 60 °C and 14 h, respectively. In addition, the nutritional analysis allowed to determine that the dried jicama is rich in carbohydrates, fiber, potassium, phosphorus, calcium and vitamin C. Becoming a nutritional alternative, which contributes to food sovereignty, allowing to improve the economy of farmers by adding added value to jicama. Keywords: jicama, dehydration, hedonic scale, organoleptic analysis, temperature.